Engineering the catalytic properties of CeO2 catalyst in HCl-assisted propane dehydrogenation by effective doping: A first-principles-based microkinetic simulation - Jan, Faheem; Yang, Min; Zhou, Nuodan; Sun, XiaoYing; Li, Bo (Frontiers in Chemistry, 2023)
HCl-assisted propane dehydrogenation (PDH) is an attractive route for propene production with good selectivity. In this study, the doping of CeO2 with different transition metals, including V, Mn, Fe, Co, Ni, Pd, Pt, and Cu, in the presence of HCl was investigated for PDH. The dopants have a pronounced effect on the electronic structure of pristine ceria that significantly alters the catalytic capabilities. The calculations indicate the spontaneous dissociation of HCl on all surfaces with a facile abstraction of the first hydrogen atom except on V- and Mn-doped surfaces. The lowest energy barrier of 0.50 and 0.51eV was found for Pd- and Ni-doped CeO2 surfaces. The surface oxygen is responsible for hydrogen abstraction, and its activity is described by the p-band center. Microkinetics simulation is performed on all doped surfaces. The increase in the turnover frequency (TOF) is directly linked with the partial pressure of propane. The adsorption energy of reactants aligned with the observed performance. The reaction follows first-order kinetics to C3H8. Furthermore, on all surfaces, the formation of C3H7 is found as the rate-determining step confirmed by the degree of rate control (DRC) analysis. This study provides a decisive description of catalyst modification for HCl-assisted PDH.